2021
DOI: 10.1017/s0007114521005134
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood pressure and BMI in young adult population: a national-level assessment in Bangladesh

Abstract: Young adulthood is a crucial period for major physiological transitions. Environmental changes associated with these transitions can influence health behaviour and health (e.g., poor diet, high body weight and elevated blood pressure (EBP)). Excess body weight can lead to EBP; however, little is known about this relationship among young adults in developing countries. Focusing on Bangladesh, this study assessed the association between body mass index (BMI) and BP metrics (systolic BP [SBP], diastolic BP [DBP],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Moreover, multivariable log-binomial regression analysis indicated that obese students had roughly threefold increased prevalence of having high blood pressure compared to those with a normal BMI, which aligns with previous findings [ 18 , 19 ]. These findings are consistent with the results from earlier studies [ 32 34 ]. On the other hand, the pathophysiology of hypertension in patients with obesity is complex and still an area of research.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, multivariable log-binomial regression analysis indicated that obese students had roughly threefold increased prevalence of having high blood pressure compared to those with a normal BMI, which aligns with previous findings [ 18 , 19 ]. These findings are consistent with the results from earlier studies [ 32 34 ]. On the other hand, the pathophysiology of hypertension in patients with obesity is complex and still an area of research.…”
Section: Discussionsupporting
confidence: 94%